Farelo de algodão como sucedâneo do farelo de soja em rações para tilápia do Nilo - Kleemann, Geisa Karine [UNESP]; Silva, Maely Dal Pai [UNESP]; Pezzato, Luiz Edivaldo [UNESP]; Teixeira, Caroline Pelegrine [UNESP]; Padovani, Carlos Roberto [UNESP]; Barros, Margarida Maria [UNESP] (My University, 2011)
This feeding trial was conducted to evaluate the effects of partial replacement of soybean meal by cottonseed meal and the effects of two feed processing methods, pelleting and extrusion, in Nile tilapia feeds. The cottonseed meal was solvent-processed and contained no amount of free gossypol and 0.0987% of total gossypol. The diets were formulated to contain 30% digestible protein and 3200kcal/kg digestible energy and the supplemental amino acids were added based on the ideal protein concept. In the experimental diets, soybean meal protein was gradually replaced by cottonseed meal protein (0, 12.5, 25 and 50%), which corresponded to 0, 8, 16 and 32% of inclusion of cottonseed meal in the diets, respectively. 192 Nile tilapia fingerlings with an average weight of 4.60±0.23g, were distributed in 32 200-L cylindrical net-tanks, on a recirculating water system and were fed to apparent satiation four times a day, during 95 days. The experiment was conducted in a 4x2 factorial, in a completely randomized design, with four replicates. After 95 days, no significant differences for growth performance and physiological responses of fish fed diets containing cottonseed meal in comparison to fish fed the diets based on soybean meal were observed. Cottonseed meal (0% free gossypol) can replace 50% of soybean meal protein in the diet (32% of inclusion level in the diet) of Nile tilapia if supplemented with synthetic lysine, without impared growth performance, hematology and intestinal morphology.

Objetivou-se neste experimento avaliar a substituição parcial do farelo de soja pelo farelo de algodão e dois métodos de processamento, peletização e extrusão, em rações para a tilápia do Nilo. As rações foram formuladas para conter 30% de proteína digestível e 3200kcal/kg de energia digestível e a suplementação de aminoácidos foi baseada no conceito de proteína ideal. A proteína do farelo de soja foi gradualmente substituída pela proteína do farelo de algodão (0; 12,5; 25 e 50%), o que correspondeu a 0, 8, 16 e 32% de inclusão de farelo de algodão nas rações, respectivamente. O farelo de algodão não apresentou gossipol livre e 0,0987% de gossipol total. Foram distribuídos em 32 tanques-rede cilíndricos (200L) em sistema de recirculação de água, 192 alevinos de tilápia do Nilo com peso médio inicial de 4,60±0,23g, alimentados até a saciedade aparente quatro vezes ao dia, durante 95 dias. A experimentação foi conduzida em esquema fatorial (4x2), no delineamento inteiramente casualizado balanceado com quatro repetições. Após 95 dias, não foram observadas diferenças nos parâmetros de desempenho produtivo e respostas fisiológicas dos peixes alimentados com as rações contendo farelo de algodão, em comparação aos peixes alimentados com as rações à base de farelo de soja. O farelo de algodão (0% de gossipol livre) pode compor 32,0% da ração para tilápia do Nilo, em substituição a 50,0% da proteína do farelo de soja, quando suplementado com lisina, sem afetar o desempenho, hematologia e morfologia intestinal dos animais em crescimento.
Cottonseed meal as a substitute for soybean meal in ile tilapia diet
Keywords: Gossypol; Growth performance; Hematology; Lysine; Morphology; Oreochromis niloticus; Desempenho produtivo; Gossipol; Hematologia; Lisina; Oreochromis niloticus